2010
DOI: 10.1038/jcbfm.2009.272
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor of Plasminogen Activator Inhibitor-1 Provides Antithrombotic Benefits Devoid of Bleeding Effect in Nonhuman Primates

Abstract: Inhibition of plasminogen activator inhibitor (PAI)-1 is useful to treat several disorders including thrombosis. An inhibitor of PAI-1 (TM5275) was newly identified by an extensive study of structure-activity relationship based on a lead compound (TM5007) which was obtained through virtual screening by docking simulations. Its antithrombotic efficacy and adverse effects were tested in vivo in rats and nonhuman primates (cynomolgus monkey). TM5275, administered orally in rats (1 to 10 mg/kg), has an antithrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
108
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 29 publications
1
108
0
Order By: Relevance
“…After sorting, 1x10 5 cells were seeded and cultured for 24 h. Then, medium was changed to DMEM with or without 10 nM TM5275 for 24 h, and the supernatants were collected (43). As shown in Fig.…”
Section: Exposing Aldh1-low Cells To Tm5275 a Small Molecule Inhibitmentioning
confidence: 99%
“…After sorting, 1x10 5 cells were seeded and cultured for 24 h. Then, medium was changed to DMEM with or without 10 nM TM5275 for 24 h, and the supernatants were collected (43). As shown in Fig.…”
Section: Exposing Aldh1-low Cells To Tm5275 a Small Molecule Inhibitmentioning
confidence: 99%
“…Although an inhibitor for PAI-1 that neutralizes the activity of both PAI-1 in complex with VN and of free PAI-1 may yield the most effective inhibition, it is still possible that selective inhibition of free PAI-1 could provide therapeutic benefit. Several studies with inhibiting antibodies and small molecules against PAI-1 have shown effects in different animal models of fibrinolysis (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). We are not aware of a PAI-1 inhibitor that has been tested in patients, but the low molecular weight PAI-1 inhibitor PAI-749 (diaplasinin) has been tested ex vivo in human blood using the Badimon chamber and was found not to have an effect on in vitro or ex vivo thrombus formation or fibrinolysis in the presence or absence of tPA (43,44).…”
mentioning
confidence: 99%
“…[2][3][4][5][6] It is already known that small molecules including peptides can inhibit PAI-1 activity by entering into the cleft of the PAI-1 molecule as a mock substance. [25][26][27][28] As the extracts from heshiko and narezushi contain a large amount of peptides, 19,20 therefore, direct PAI-1 inhibition by heshiko and narezushi extracts is proposed as a possible mechanism to explain the reduced PAI-1 activity of rats shown in Table 3. Next, the PAI-1 inhibitory activity of the heshiko and narezushi extracts was examined by mixing active PAI-1 solution with the heshiko and narezushi extracts.…”
Section: Pai-1 Activity Is Regulated By Various Factors and Ismentioning
confidence: 99%
“…shown to be PAI-1 inhibitors, 26,27 we examined changes in the PAI-1 inhibitory activity of these extracts by digestion with proteases.…”
Section: Pai-1 Activity Is Regulated By Various Factors and Ismentioning
confidence: 99%
See 1 more Smart Citation